Leading Pharmaceutical Innovation How to Win the Life Science Race - Gassmann, Oliver (Springer International Publishing, 2018)
This book investigates and highlights the most critical challenges the pharmaceutical industry faces in an increasingly competitive environment of inflationary R&D investments and tightening cost control pressures. The authors present three sources of pharmaceutical innovation: new management methods in the drug development pipeline; new technologies as enablers for cutting-edge R&D; and new forms of cooperation and internationalization, such as open innovation in the early phases of R&D. New models and methods are illustrated with cases from Europe, the US, and Asia. This third fully revised edition was expanded to reflect the latest updates in open and collaborative innovation, the greater strategic importance of venture capital and early-stage investments, and the new range of emerging technologies now being put to use in pharmaceutical innovation. Health care innovation is possibly the greatest opportunity and challenge of our generation. This important book shows how pharmaceutical companies will continue to play an instrument role in making our lives better. Stefan Thomke, William Barclay Harding Professor of Business Administration, Harvard Business School Very comprehensive review and analysis of current challenges for the biopharmaceutical industry. To stay competitive in this new technology driven environment, the industry started to develop new partnership models to close the innovation gap and provide patients with the relevant healthcare toolkits at the convergence of pharmaceuticals, diagnostics and IT technologies. Very exciting times ahead well depicted in this book! Karima Boubekeur, VP Emerging Portfolio and Search & Evaluation, AstraZeneca Great. The 3rd edition is not only an update. It's an outstandingly featured summary on the challenges of pharma innovation. Eckard von Keutz, SVP and Head of Early Development, Bayer Healthcare.